In search of ancient kings : Egúngún in Brazil - Willson, Brian (University Press of Mississippi, 2021)
"The Egúngún society is one of the least-studied and written-about aspects of African diasporic spiritual traditions. It is the society of the ancestors, the society of the dead. Its primary function is to facilitate all aspects of ancestor veneration. Though it is fundamental to Yorùbá culture and the Ifá/Òrìṣà tradition of the Yorùbá, it did not survive intact in Cuba or the US during the forced migration of the Yorùbá in the Middle Passage. Taking hold only in Brazil, the Egúngún cult has thrived since the early 1800s on the small island of Itaparica, across the Bay of Saints from Salvador, Bahia. Existing almost exclusively on this tiny island until the 1970s (migrating to Rio de Janeiro and, eventually, Recife), this ancient cult was preserved by a handful of families and flourished in a strict, orthodox manner. Brian Willson spent ten years in close contact with this lineage at the Candomble temple Xango Cá Te Espero in Rio de Janeiro and was eventually initiated as a priest of Egúngún. Representing the culmination of his personal involvement, interviews, research, and numerous visits to Brazil, this book relates the story of Egúngún from an insider's view. Very little has been written about the cult of Egúngún, and almost exclusively what is written in English is based on research conducted in Africa and falls into the category of descriptive and historical observations. Part personal journal, part metaphysical mystery, part scholarly work, part field research, and part reportage, In Search of Ancient Kings illuminates the nature of Egúngún as it is practiced in Brazil"--